Surgeons, Intensivists, and Discretion to Refuse Requested Treatments - Wicclair, Mark R. (The Hastings Center report, 2014)
Physicians are expected to engage patients as partners in identifying the possible benefits and harms associated with treatment options and selecting from among medically appropriate treatment options, rather than simply dictating what treatments patients will and will not receive. This collaborative model reflects the recognition that citizens in multicultural societies have diverse values and are likely to have different views about whether the possible benefits of a medical intervention outweigh the possible harms. However, there are circumstances in which the collaborative process breaks down due to irresolvable disagreement. Especially challenging are cases in which patients are expected to die if they do not receive a treatment and either the patients or their surrogates insist on the treatment despite the physician's belief that providing it is ill advised. The source of disagreement is often differing appraisals of the risks and potential benefits. In such cases, physicians generally judge that there is insufficient likelihood or magnitude of benefit to justify the burdens or expense of treatment, while patients or surrogates believe that the small chance of preventing the patient's death is sufficient to justify the costs and potential burdens to the patient. There is a perception that surgeons enjoy considerable discretion in deciding when the risks of a procedure outweigh the expected benefits. An important contrast can be drawn between surgeons and intensivists—physicians who specialize in the medical management of critically ill patients. We will argue that there are good reasons for subjecting the decisions of both surgeons and intensivists to some oversight. We begin by showing that, for many cases, major professional society guidelines for intensivists recommend oversight via a procedural mechanism rather than unilateral decision-making by individual clinicians. Next, we present reasons for adopting a procedural approach to dispute resolution, and we argue that these reasons apply to situations in which intensivists believe that patients or surrogates are requesting inappropriate life support as well as to many disagreements between surgeons and surrogates. Finally, we present and respond to several objections.